Penerapan Metode Pembelajaran Student Teams Achievement Division (Stad) Untuk Meningkatkan Keaktifan Belajar Pada Mata Pelajaran IPS Siswa Kelas VII SMP Negeri 2 JatinomTahun Ajaran 2016/2017 - NUR FITRIANA, IMA; , Drs. Budi Sutrisno, M.Pd (2017)
This research of class action aims to improve students' learning activeness in social science subjects through Student Teams Achievement Division (STAD) learning method. This research of class action is a type of qualitative data, it is the data in the form of data and sentences. The subjects of the study were class VII D SMP Negeri 2 Jatinom which amounted to 31 students. Methods of data collection using observation methods, interviews, field notes and documentation. There are four stages in this study procedures, there are action planning, action implementation, observation, reflection. Data analysis techniques used consist of data reduction, data presentation, and data verification. The results of this study indicate that the application of Student Teams Achievement Division (STAD) can effectively improve students' learning activity in social science subjects class VII D SMP N 2 Jatinom academic year 2016/2017. This is evidenced before the action, the percentage of students 'learning activity is only 23.65%, reaching 58.60% and after the II cycle action, students' learning activity and overall increased to 82.23%.